Social Capital and Civic Engagement in Times Of Tension: An Evidence from Interethnic Relation Developed in Stella Maris Credit Union Pontianak, West Kalimantan - Alanuari Alanuari; Mohammad Iqbal Ahnaf (Graduate Program of Pontianak Institute of Islamic Studies, 2020)
This paper begins by questioning the sustainability of civic engagement with the notion of ‘social capital’ as the key concept of Peace and Conflict Studies. The main question is: to what extent does socio-political tension affect forms of civic engagement? This paper examines interethnic relations (Dayak, Malay, Chinese, and Javanese) developed in the Stella Maris Credit Union (SMCU) in Pontianak, West Kalimantan, Indonesia under the context of ethnic tension. SMCU is a microfinance association where people with various backgrounds (religion, race, and ethnicity) interact in an economic community, sharing benefits and values. In the beginning, SMCU was initiated as an economic program of Stella Maris Catholic Church in North Pontianak. This church did not only serve the church members, but also for all ethnicities and religions through Pontianak. As a site drastically impacted by ethnic conflict in the post-Suharto era, Pontianak recently has been growing as a city of ethnic diversity. However, the recent rise of ethnic tension has contested this growing multiethnic coexistence. It is important to see the strength of civic engagement in responding to issues of conflict in a multiethnic society. This study explores SMCU members and their personal experiences, wondering whether the tension may or may not affect the forms of civic engagement. It argues civic engagement can sustain under the moment of socio-political tension. Developing economy and peace education are the main reasons for interethnic relations among SMCU members. Moreover, although there are treats for the plural society, experiencing diversity in the form of associational and neighborhood relations contributes to social coexistence. This study finds that forms of civic engagement among the members shape expressions and attitudes of resilience in facing social tension.